(untitled) (Journal of Pedagogical Inventions and Practices, 2021)
Educating young people in the spirit of patriotism is a multi – stage, systematic, purposeful and coordinated activity of state bodies, public associations and organizations aimed at forming a sense of loyalty to the motherland in young people, regardless of nationality, language and profession, educating them as individuals capable of fulfilling their civil duties and constitutional obligations, protecting the interests of society and In this regard, of course, we can say that the role of the family and society is separate. In particular, the main goal of educating young people in the spirit of patriotism is to show activity in various sectors of society, especially in the types of civil service associated with the military sphere, to be faithful to the Constitution and military duty in a peaceful and military environment, to form in them such important features as high responsibility and responsibility for the In this article, the mutual differences between family and public education in the upbringing of young people in the spirit of patriotism and the principles of ensuring their cohesion are discussed